Estimation of threshold fluence, absorption coefficient and thermal loading of car coated substrate in laser paint removal - Mohammad Khairul Azhar Abdul Razab; Mohamad Suhaimi Jaafar; Azhar Abdul Rahman; Syahrul Affandi Saidi (2014)
Threshold fluence (FT), absorption coefficient (α) and thermal loading (γ) were estimated on three types of car coated substrate by applying Beer-Lambert law. Cynosure Cynergy Pulse Nd:YAG was using to irradiate 54 substrate samples and the depth of coating removed (d) was obtained by using Alicona IFM G4. Depth of coating removed (d) versus laser fluence (F) graphs was plotted for each pulse width (PW), repetition rate (RR) and beam size (BS) considered by measuring the average of coating removal efficiency (ε). The best interceptions of certains ε with their X-axis were selected for each sample A, B and C, representing their general FT, α and γ respectively.